Удмуртские народные мифы и легенды - Кралина Надежда Петровна (Удмуртия, 2016)
Экземпляры: (20190425) / Инвентарный номер: 50220 / Цена: 432.00 / Сис.шифр: 82.3(2) / Авт.знак: У 30 / ГРНТИ: 17 / ББК: 82.3(2Рос=Удм).06